Applications of Herbal Medicine to Treat Autosomal Dominant Polycystic Kidney Disease - Shao, Guangying; Zhu, Shuai; Yang, Baoxue (Frontiers in Pharmacology, 2021)
Autosomal dominant polycystic kidney disease (ADPKD) is a common hereditary kidney disease. It is featured as multiple progressively enlarged fluid-filled cysts in both kidneys, which destroys the surrounding normal kidney structure, resulting in the loss of renal function. Eventually, ADPKD will develop into end-stage renal disease (ESRD), which puts great burden on patients and society. There is no effective intervention can be used clinically at present besides hemodialysis and kidney transplant. Therefore, looking for effective ADPKD therapeutic drugs is important. Herbal medicines showed their great effect in multiple diseases, such as cancer, diabetes and mental disorders, which might also be good candidate drugs for ADPKD treatment. Currently, many studies have reported that the compounds from herbal medicines contributed to inhibit the growth of renal cysts and alleviate the progression of ADPKD, such as triptolide, curcumin, ginkolide B, steviol, G. lucidum triterpenoids, Celastrol, saikosaponin-d, Sparganum stoloniferum Buch.-Ham and Cordyceps sinensis by similar or different mechanisms. These studies suggest that herbal medicines would be a promising type of ADPKD drugs and can provide new inspiration for clinical therapeutic strategy. This review summarizes the pharmacological effects of the herbal medicines on ADPKD and their underlying mechanisms in vivo and in vitro ADPKD models.